Circular Human Resources: Employee Retention Strategy through an Inter-Organizational “Talent Sharing” Model (Focus: Talent Sharing to Prevent Layoffs During Crisis) - Devi Nor Holizhoh; Farah Zhafira Mellyana Pratiwi; Vita Fatmawati; Mochammad Isa Anshori (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2026)
Global economic crises, technological disruption, and organizational uncertainty have driven companies to adopt efficiency measures through layoffs, which may reduce human capital value and weaken organizational sustainability. This study aims to analyze and formulate a Circular Human Resources (Circular HR) model based on talent sharing as an employee retention strategy during crises. The research employs a Systematic Literature Review (SLR) approach guided by PRISMA to identify, select, and synthesize relevant scholarly literature on talent management, sustainable HRM, and inter-organizational collaboration. The findings indicate that inter-company talent sharing enables flexible workforce redistribution, allowing organizations to maintain employment relationships without resorting to layoffs. The effectiveness of this model is influenced by regulatory frameworks, organizational readiness, and the level of trust and collaboration among participating firms. Furthermore, the model contributes to skill enhancement, cost efficiency, and strengthened organizational resilience in times of crisis. This study offers a conceptual framework that integrates circular economy principles with collaborative human resource management strategies, providing practical implications for organizations and policymakers in designing a more adaptive and sustainable employment system.